THE IMPACT OF MIGRAINE IN CHILDREN AND ADOLESCENTS ON THE DEVELOPMENT OF MENTAL DISORDERS - Hanna Nowicka; Emmanuelle Ordon; Maria Joks; Dominika Liszka; Kamila Ostromecka; Paweł Grzesikowski; Kinga Bekier; Jan Krzysztof Górski; Jakub Kubiak; Paulina Klich (International Journal of Innovative Technologies in Social Science, 2025)
Objective: Migraine is a common cause of pain in children and adolescents. There has been a consistent rise in the number of diagnoses over the years, which means that the problem is becoming progressively more frequent. The increase in psychiatric diagnoses in children and adolescents, we have raised a question whether there is a connection between these two issues. Methods: Materials and methods An electronic literature search was performed using PubMed. Search terms included “migraine”, “depression”, “anxiety” “bipolar disease”, “obsesive-compulsive disorder”, “anorexia”, “attention deficit hyperactivity disorder”, “insomnia”, “children”, “adolescents”, “psychiatric disorders” as keywords. The review focused on articles published in English and Polish from their inception until 2025. Key Findings: Migraine frequently co-occurs with symptoms of anxiety and depression. A higher incidence of bipolar disorder, OCD, and ADHD has been reported in children with migraine. It is possible that migraine and these conditions share common pathophysiologies. Experiencing chronic pain in childhood is also associated with sleep and eating difficulties, reducing the quality of life of paediatric patients. Conclusion: We present statistics on the co-occurence of these disorders with migraine, as well as reports on the possibility of common pathophysiological substrates and mutual connections, which indicate a significant impact of migraine on the development of mental disorders. However, still more research is needed to obtain valid information on the discovered relationships that would surely help to create more effective and targeted treatment and certainly provide whole-person care for young patients.